2018
DOI: 10.1111/odi.12938
|View full text |Cite
|
Sign up to set email alerts
|

TIMP‐1 association with collagen type I overproduction in hereditary gingival fibromatosis

Abstract: We report that fibrosis in HGF gingival tissues is associated with increased synthesis of HSP47. This finding was confirmed by an in vitro study, where excessive production of collagen I was associated with increased synthesis of HSP47, TGF-β1 and CTGF by HGF gingival fibroblasts. Moreover, the shift in the TIMP-1/MMP-1 ratio identifies increased synthesis of TIMP-1 as one of the processes associated with collagen I overproduction in HGF fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
12
1
3
Order By: Relevance
“…However, this function and molecular pathogenesis of REST -associated HGF remain to be elucidated. A significant overexpression of profibrotic genes, including type I collagen, HSP47, TGF-β1, IL-6, CTGF, and TIMP-1, has been demonstrated in HGF gingival fibroblasts compared to controls, while production of proteolytic enzymes, MMP-1 and MMP-2, are reduced (Martelli-Junior et al 2003; Gawron et al 2018). Much evidence has indicated that the contribution of REST repression to basal expression levels is context dependent (Chen et al 1998; Cheong et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, this function and molecular pathogenesis of REST -associated HGF remain to be elucidated. A significant overexpression of profibrotic genes, including type I collagen, HSP47, TGF-β1, IL-6, CTGF, and TIMP-1, has been demonstrated in HGF gingival fibroblasts compared to controls, while production of proteolytic enzymes, MMP-1 and MMP-2, are reduced (Martelli-Junior et al 2003; Gawron et al 2018). Much evidence has indicated that the contribution of REST repression to basal expression levels is context dependent (Chen et al 1998; Cheong et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in the presence of 10 μg/ml nystatin until passage 2 to prevent fungal contamination. The isolation procedure and the homogeneity of GF cultures have been standardized and described previously (22). GECs were used for experiments at passage 2 and GFs were used between passages 4 and 9.…”
Section: Methodsmentioning
confidence: 99%
“…The pathophysiologic mechanisms underpinning HGF remain elusive. Nonetheless, extracellular matrix overproduction involving major component of collagen type I was believed to be a cause of the gingival fibroblast overgrowth phenotype; on the other hand, increased production of TIMP-1 appeared to be associated with excessive collagen I accumulation in HGF fibroblasts [24,25]. Also, Martelli-Junior and coworkers claimed that TGF-β1, IL-6 and perhaps other specific growth factors overproduction in fibroblasts might play pivotal roles in unwarranted collagen I synthesis [26].…”
Section: Figure 1 a Chinese Pedigree With Non-syndromic Hereditary Gingival Fibromatosis (Hgf)mentioning
confidence: 99%